THE IDENTIFICATION OF THE PATTERN OF JAVA ISLAMIC CITY CATUR GATRA TUNGGAL IN LAMONGAN - Hammam Rofiqi Agustapraja; Siti Suwaibatul Aslamiyah (Journal of Islamic Architecture, 2022)
Catur Gatra Tunggal is a pattern of urban planning in Java that originated from the establishment of the Islamic Mataram kingdom in the 18th and 19th centuries which influenced urban planning in Java in particular. The purpose of the study was to identify the old urban planning pattern in Lamongan Regency, which has an essential role in the spread of Islam in Java, especially East Java. The method used in this research is descriptive qualitative with field observations and surveys to identify the elements that makeup Catur Gatra Tunggal pattern compared to the theory of public space and architectural preservation. The study results found that Catur Gatra Tunggal pattern was still well identified with its constituent elements; Alun-Alun, Pendhopo Lokatantra, Traditional Markets, and the Great Mosque. It is hoped that the results of this study will be used as a reference in the development of Alun-Alun area regarding buildings and values that must be maintained to remain a pearl of local cultural wisdom that must be held.